2023
DOI: 10.25130/tjphs.2012.8.1.2.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of conventional renal function tests in β-thalassemia major patients in Nineveh province

Zaid Muwafaq Younus,
Yusra Ahmed Hussein Alhially,
Ahmed Yahya Dallal Bashi

Abstract: β-thalassemia is an inherited anemia, caused by impaired β-globin chain synthesis. The disease leads to serious health problems unless treated by regular blood transfusion and iron chelating therapy. However, complications from continuous therapy may arise due to iron overload and toxicity of iron chelating therapy, it may affects many organs in the body including the renal system. The present study was directed to study the changes in conventional renal function tests that may occur in β-thalassemia patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study revealed a notable rise in creatinine, while no significant alterations were observed in K [32]. Moreover, the investigation conducted by Younus et al in Iraq revealed noteworthy age-related elevations in creatinine among thalassemia patients [52]. The study shows urinary β2M increases with age [53].…”
Section: Discussionmentioning
confidence: 63%
“…The study revealed a notable rise in creatinine, while no significant alterations were observed in K [32]. Moreover, the investigation conducted by Younus et al in Iraq revealed noteworthy age-related elevations in creatinine among thalassemia patients [52]. The study shows urinary β2M increases with age [53].…”
Section: Discussionmentioning
confidence: 63%